2019
DOI: 10.1021/acs.cgd.8b01488
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study for Comprehensive Understanding of Solid-State Polymorphic Transitions of Nicotinamide/Pimelic Acid Cocrystals

Abstract: Solid-state polymorphic transition (SSPT) has been regarded as an interesting research subject for a long time, but kinetics and the mechanism of these phase transitions are still not fully understood. Particularly, kinetic studies on the SSPT process of cocrystals are not widely reported even though extensive novel cocrystal polymorphs have been discovered over the recent decades. Herein we presented a comprehensive kinetic study of the enantiotropic polymorphic system of 1:1 nicotinamide (NA)–pimelic acid (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…This slow conversion of Form II → Form I at room temperature has been previously noted. 42 In full agreement with stability test experiments, slurrying 1 : 1 mixtures of Form I and Form II in a range of solvents also led to formation of pure Form I , ESI S1.3,† lending support to the thermodynamic stability of Form I over Form II at room temperature. Moreover, we note previous high temperature slurry experiments, which indicated that the reverse transformation of Form I → Form II occurs when slurried > 85 °C.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…This slow conversion of Form II → Form I at room temperature has been previously noted. 42 In full agreement with stability test experiments, slurrying 1 : 1 mixtures of Form I and Form II in a range of solvents also led to formation of pure Form I , ESI S1.3,† lending support to the thermodynamic stability of Form I over Form II at room temperature. Moreover, we note previous high temperature slurry experiments, which indicated that the reverse transformation of Form I → Form II occurs when slurried > 85 °C.…”
supporting
confidence: 58%
“…Form I of NA:PA is reported to be thermodynamically stable under ambient conditions, with Form II becoming the stable form at elevated temperatures. 40,42 Both forms can be prepared by ball milling: Form I is reportedly obtained by neat grinding at ambient temperature 40 and, as we have found in this work (ESI S2 †), Form II is obtained by ball milling at elevated temperatures. Consistent with the literature, 40 our differential scanning calorimetry (DSC) measurements of Form I, Fig.…”
mentioning
confidence: 67%
“…The kinetic parameters of the solid-state phase transformation reactions such as mineral, alloy glass and pharmaceutical ingredient phase transformations are always obtained via using non-isothermal technique. [54][55][56][57][58][59][60] Except the Kissinger and Ozawa methods, a special method that only suitable for investigating heterogeneous solid-state reactions was developed based on Avrami law (Equation 40), which could be used to describe most solid phase transformation reactions.…”
Section: Solid Phase Transformationmentioning
confidence: 99%
“…Therefore, a more pertinent description would be the RTform is more stable below transition temperature (42 °C), and HT is more stable above transition temperature and the activation energy of RT-form ↔ HT-form kinetics is on the order of 30−40 kJ/mol. 38 The magnitude of activation energy for the AGL-P system is significantly less as compared to a (1:1) nicotine−pimelic acid cocrystal, 83 which was reported to exhibit a solid-state phase transition via nucleation and growth mechanism, unlike the current system. In summary, all this information refers to the point that the interplay of thermodynamic stability and kinetic activation barrier is very delicate for the AGL-P system.…”
Section: Discovery Of Polymorphism and Their Thermalmentioning
confidence: 92%